Model Pembelajaran Bahasa Arab Multiliterasi Berbasis Kearifan Lokal Dan Moderasi Islam di Perguruan Tinggi Negeri - Andy Hadiyanto; Siti Maria Ulfah; Cendra Samitri (Universitas Negeri Jakarta, 2020)
This study aims to develop a multiliteration of Arabic language learning based on local wisdom in public universities that are valid, effective, efficient, and practical so that it can be used as an alternative to other learning models applied by Arabic lecturers. This study uses a qualitative approach with the pattern